Research on the Path of Innovation and Entrepreneurship Education in Local Applied Universities under the "Cloud" Mode (Contemporary Education and Teaching Research, 2023)
The "cloud" model is one of the important exploration directions of innovation and entrepreneurship education in colleges and universities. Local applied colleges and universities are constantly trying to reform the innovation and entrepreneurship education model. This study aims to explore the path of innovation and entrepreneurship education in local applied colleges and universities under the "cloud" model, in order to improve the effectiveness and effectiveness of innovation and entrepreneurship education. Through the practical case and qualitative analysis of innovation and entrepreneurship education in colleges and universities, this study deeply analyzes the practical achievements and bottlenecks of innovation and entrepreneurship education in local applied colleges and universities under the "cloud" mode. On the basis of summarizing, this paper puts forward the practical mode of innovation and entrepreneurship education path in local applied colleges and universities under the "cloud" mode with "production, teaching, research and social service" as the fulcrum, that is, through the development of productive practice projects, promote the differentiated development of students, and solve the problem of combining teaching practice and entrepreneurship by means of school-enterprise cooperation.This research has important practical significance for promoting the continuous innovation and upgrading of innovation and entrepreneurship education in colleges and universities.